2020
DOI: 10.1002/jper.19-0743
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy levels of gingival crevicular fluid matrix metalloproteinases‐8 and ‐9 are associated with the severity of periodontitis and the development of gestational diabetes mellitus

Abstract: Background Gestational diabetes mellitus (GDM) is increasing worldwide and women with a history of GDM are at risk of developing type 2 diabetes which is a risk factor for periodontitis. The aim of this study was to explore the association between the concentrations of matrix metalloproteinase (MMP)‐8 and ‐9 in gingival crevicular fluid (GCF) during early pregnancy with the periodontal diagnosis and the risk of GDM development. Methods A prospective cohort study, including 314 women, enrolled at 11 to 14 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
0
31
1
3
Order By: Relevance
“…Recently, Trombelli et al 10 stated that BOP levels are mostly a sign of the extent of gingival inflammation rather than the severity of the periodontal inflammatory condition. In addition, previous studies have shown that aMMP‐8 levels in oral fluids (saliva, mouthrinse, GCF, and PISF) correlate well with clinical periodontal parameters and periodontal disease severity 15‐37,49 . In the present study, the association between salivary aMMP‐8 levels and BOP levels was weak, even if adjusted for possible confounding factors such as smoking.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, Trombelli et al 10 stated that BOP levels are mostly a sign of the extent of gingival inflammation rather than the severity of the periodontal inflammatory condition. In addition, previous studies have shown that aMMP‐8 levels in oral fluids (saliva, mouthrinse, GCF, and PISF) correlate well with clinical periodontal parameters and periodontal disease severity 15‐37,49 . In the present study, the association between salivary aMMP‐8 levels and BOP levels was weak, even if adjusted for possible confounding factors such as smoking.…”
Section: Discussioncontrasting
confidence: 55%
“…The quantitative pointof-care oral fluid aMMP-8 immunotest has been repeatedly and independently validated in Finland, Germany, Italy, Nigeria, Turkey, Netherlands and United States to successfully screen susceptible sites and patients, differentiate active and inactive periodontal and dental peri-implant sites and periodontitis and dental peri-implantitis [25,27], predict the future disease progression and monitor treatment response and maintenance therapy [25,27]. Furthermore, previous studies have shown that the aMMP-8 test could be potentially useful related to diabetes and related diseases in the medical settings [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate model which included glycemia and GCF-PlGF during early pregnancy discriminated the future development of GDM with an AUC-ROC curve of 0.897 (78.6% sensitivity and 75% specificity) [68]. Moreover, MMP-8 and MMP-9 were found to have increased in the early stages of pregnancy (<14 weeks of gestation) in women who later developed GDM [89]. In the same study, clinical periodontal parameters were positively correlated with the expression of both MMPs in GCF, and pregnant women with periodontitis stage III and IV showed increased concentrations of MMP-8 when compared with pregnancies with periodontitis stage I [89].…”
Section: Release Of Pro-inflammatory Molecules From Periodontal Inflamed Tissues and Systemic Inflammation As An Indirect Mechanism Of Asmentioning
confidence: 97%
“…Moreover, MMP-8 and MMP-9 were found to have increased in the early stages of pregnancy (<14 weeks of gestation) in women who later developed GDM [89]. In the same study, clinical periodontal parameters were positively correlated with the expression of both MMPs in GCF, and pregnant women with periodontitis stage III and IV showed increased concentrations of MMP-8 when compared with pregnancies with periodontitis stage I [89]. Thus, increases in MMP-8 and MMP-9 levels in GCF were associated with both the severity of periodontitis and GDM development.…”
Section: Release Of Pro-inflammatory Molecules From Periodontal Inflamed Tissues and Systemic Inflammation As An Indirect Mechanism Of Asmentioning
confidence: 99%